Role of Nitrogen Doping on the Performance of Carbon Nanotube Catalysts: A Catalytic Wet Peroxide Oxidation Application - Maria Martin-Martinez (2016)
Four magnetic carbon nanotube (CNT) samples (undoped, completely N-doped, and two selectively N-doped) were synthesized by chemical vapor deposition. The materials were tested in the catalytic wet peroxide oxidation (CWPO) of highly concentrated 4-nitrophenol solutions (4-NP, 5gL(-1)). Relatively mild operating conditions were considered (atmospheric pressure, T=50 degrees C, pH3), using a catalyst load of 2.5gL(-1) and the stoichiometric amount of H2O2 needed for the complete mineralization of 4-NP. N-doping was identified to influence considerably the CWPO performance of the materials. In particular, undoped CNTs, with a moderate hydrophobicity, favor the controllable and efficient decomposition of H2O2 into highly reactive hydroxyl radicals (HO.), thus showing high catalytic activity for 4-NP degradation. On the other hand, the completely N-doped catalyst, fully hydrophilic, favors a quick decomposition of H2O2 into nonreactive O-2 and H2O species. The selectively N-doped amphiphilic catalysts, that is, hybrid structures containing undoped sections followed by N-doped ones, provided intermediate results, namely, a higher N content favored H2O2 decomposition towards nonreactive H2O and O-2 species, whereas a lower N content resulted in the formation of HO., increasing 4-NP mineralization. Catalyst stability and reusability were also investigated by consecutive CWPO runs.